Involvement of the PTEN–AKT–FOXO3a pathway in neuronal apoptosis in developing rat brain after hypoxia–ischemia - Li, Deyuan (2009)
The proapoptotic function of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) phosphatase has been linked to its capacity to antagonize the phosphatidylinositol-3-kinase–Akt signaling pathway. Previous studies have shown that the Forkhead transcriptional factor (FOXO3a) is a critical effector of the PTEN-mediated tumor suppressor. However, whether the PTEN–Akt– FOXO3a pathway is involved in neuronal apoptosis in developing rat brain after hypoxia–ischemia (HI) is unclear. In this study, we generated an HI model using postnatal day 10 rats. Immunohistochemistry and western blot were used to detect the expression of total and phosphorylated PTEN, Akt, and FOXO3a, as well as its target gene Bim. We found that dephosphorylation of PTEN was accompanied by dephosphorylation of Akt and FOXO3a, which induced FOXO3a translocation into the nucleus and upregulated the expression of Bim. Furthermore, we found that PTEN inhibition by bisperoxovanadium significantly increased the phosphorylation of Akt and FOXO3a, decreased the nuclear translocation of FOXO3a, and inhibited Bim expression after HI. Moreover, the downregulation of Bim caused by PTEN inhibition attenuated cellular apoptosis in developing rat brain. Our findings suggest that the PTEN–Akt–FOXO3a pathway is involved in neuronal apoptosis in neonatal rat brain after HI. Agents targeting PTEN may offer a promise to rescue neurons from HI brain damage.